Halotolerant Exiguobacterium profundum PHM11 Tolerate Salinity by Accumulating L-Proline and Fine-Tuning Gene Expression Profiles of Related Metabolic Pathways - Patel, Vikas K.; Srivastava, Ruchi; Sharma, Anjney; Srivastava, Anchal K.; Singh, Savita; Srivastava, Alok K.; Kashyap, Prem L.; Chakdar, Hillol; Pandiyan, K.; Kalra, Alok; Saxena, Anil K. (Frontiers in Microbiology, 2018)
Salinity stress is one of the serious factors, limiting production of major agricultural crops; especially, in sodic soils. A number of approaches are being applied to mitigate the salt-induced adverse effects in agricultural crops through implying different halotolerant microbes. In this aspect, a halotolerant, Exiguobacterium profundum PHM11 was evaluated under eight different salinity regimes; 100, 250, 500, 1000, 1500, 2000, 2500 and 3000 mM to know its inherent salt tolerance limits and salt-induced consequences affecting its natural metabolism. Based on the stoichiometric growth kinetics; 100 and 1500 mM concentrations were selected as optimal and minimal performance limits for PHM11. To know, how salt stress affects the expression profiles of regulatory genes of its key metabolic pathways, and total production of important metabolites; biomass, carotenoids, beta-carotene production, IAA and proline contents, and expression profiles of key genes affecting the protein folding, structural adaptations, transportation across the cell membrane, stress tolerance, carotenoids, IAA and mannitol production in PHM11 were studied under 100 and 1500 mM salinity. E. profundum PHM11 showed maximum and minimum growth, biomass and metabolite production at 100 and 1500 mM salinity respectively. Salt-induced fine-tuning of expression profiles of key genes of stress pathways was determined in halotolerant bacterium PHM11.